Model Penerapan Kaidah Arsitektur Islam pada Bangunan Masjid di Kota Kendari - Ibrahim Akbar; Ananda Isya Anggraeni; La Pande Jurumai (LP3M Universitas Muhammadiyah Kendari, 2023)
Kendari City is a religious city. Kendari is one of the areas where the majority of the population is Muslim, accounting for around 93.27% of the total Muslim and Muslim population or around 345,778 people. For this reason, the spread of mosques in the city of kendari is quite a lot. Based on sources from the BPS province of Southeast Sulawesi in 2018, there are 371 mosques spread across kendari City. This massive distribution sometimes causes inequality. Islamic shari’a in several places of worship, namely mosques, are sometimes neglected anymore, so it is not uncommon to find mosques that are not in accordance with the principles of Islamic architecture. Therefore, it is necessary to reflect again on the application of architecture ini accordance with Islamic beliefs. The approach used ini this reseach is descriptive, obersevation, documentation and liteture study from various sources. From this approach, it can be concluded that ini general the mosques in the city of Kendari are in accordance with Shari’a and the rules of islmaic architecture.